The Influence Of Work Discipline And Leadership Style On Teacher Performance At Sma Negeri 1 Tanjng Tebat - Nabela, Ina; Markus, Markus; Sholiha, Mila (Journal of Management, Economic, and Accounting, 2025)
consisting of 62 teachers, 20 (twenty) teachers, and 6 (eight) teachers. The sample in this study consisted of 42 teachers at SMA Negeri 1 Tanjung Tebat. The t-test value for the variable "Discipline, Work" (X) is 2.645, with a significance value of 0.001. Since the significance value is less than 0.05, the correlation between Discipline, Work, and Leadership Style on Teacher Performance at SMA Negeri 1 Tanjung Tebat is significant. This means that the first hypotheses is proven. The t-value for the Leadership Style variable (X) is 1.145 with a ignificance value of 0.004. Since the significance value is less than 0.05, this means that Leadership Style influences Teacher Performance at SMA Negeri 1 Tanjung Tebat. Therefore, the second hypotheses is proven. The F-value is 15.380, with a significance value of 0.000. Since the significance value is <0.05, the third hypotheses is accepted. This means that Work Discipline and Leadership Style influence Teacher Performance at SMA Negeri 1 Tanjung Tebat. This third hypothesis is proven.